2020
DOI: 10.1108/jpbm-01-2020-2732
|View full text |Cite
|
Sign up to set email alerts
|

Brand co-creation through participation of organization, consumers, and suppliers: an empirical validation

Abstract: Purpose The purpose of this paper is to empirically validate the role of different stakeholders in a co-creation context. In this paper, a new triadic brand co-creation concept has been presented highlighting why consumers participate in brand co-creation, what is the role of the organizing company and what is the role of suppliers in such event and what are the benefits each of these three stakeholders receives in-turn of participating in such an event. Design/methodology/approach A quantitative approach ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 143 publications
(181 reference statements)
0
10
0
Order By: Relevance
“…As such, perceived brand value is also conceptualized as consumers' overall evaluation of brands, as manifested by the perceived benefits given by brands, which plays a considerable role in consumers' decision-making processes (Cheung et al, 2020b;France et al, 2020). Recent studies have found a relationship between value co-creation and perceived brand value, positing perceived brand value as a business outcome of value co-creation activities (France et al, 2018(France et al, , 2020Sarkar and Banerjee, 2020). For example, France et al (2018) found the importance of consumers' value co-creation behaviours, as manifested by their intention in creating ideas, feedback and self-developed content for brands on social-media platforms, in driving consumers' perceived brand value.…”
Section: Perceived Brand Valuementioning
confidence: 99%
“…As such, perceived brand value is also conceptualized as consumers' overall evaluation of brands, as manifested by the perceived benefits given by brands, which plays a considerable role in consumers' decision-making processes (Cheung et al, 2020b;France et al, 2020). Recent studies have found a relationship between value co-creation and perceived brand value, positing perceived brand value as a business outcome of value co-creation activities (France et al, 2018(France et al, , 2020Sarkar and Banerjee, 2020). For example, France et al (2018) found the importance of consumers' value co-creation behaviours, as manifested by their intention in creating ideas, feedback and self-developed content for brands on social-media platforms, in driving consumers' perceived brand value.…”
Section: Perceived Brand Valuementioning
confidence: 99%
“…On the other hand, instead of measuring the scale of CBC behavior directly, some researchers (e.g. Hsieh and Chang, 2016; Sarkar and Banerjee, 2020) also applied three dimensions of engagement (vigor, dedication and absorption) to illustrate the psychological aspects of the CBC.…”
Section: Resultsmentioning
confidence: 99%
“…Self-determination theory is adopted to demonstrate that the satisfaction of psychological needs (autonomy, relatedness and competence) provide personal motivation and have a significant role in the internalization process of self-motivation of CBC (Hsieh and Chang, 2016; Sarkar and Banerjee, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Co-creation research is dominated by empirical insights concerned with how organisations encourage and leverage brand conversations to enhance brand values and equity (Alam, 2020). France et al (2015) indicated that co-creation behaviours are customer-led and are predicated on pre-existing brand relationships (Sarkar and Banerjee, 2020). These are further categorised by strong emotions and are indicative of the fact that customers are no longer satisfied as dormant partners in brand development (Sarkar and Banerjee, 2019).…”
Section: Co-creationmentioning
confidence: 99%
“…Brands have become the focal points of consumers’ lives (Handa and Ahuja, 2020). They are an intrinsic part of an individual’s consumption journey and are bound in social exchange (Eng and Jarvis, 2020); engagement with them offers individuals a myriad of opportunities for social exchange (Sarkar and Banerjee, 2020). Brand managers have been keen to capitalise on the information that stems from these social exchanges (Thomas et al , 2020; Xiao et al , 2020) and one pertinent area in this context is co-creation (Sarkar and Banerjee, 2019; Sharma et al ,2020).…”
Section: Introductionmentioning
confidence: 99%